2005
DOI: 10.1245/aso.2005.03.536
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Regression and Autoimmunity in Patients Treated With Cytotoxic T Lymphocyte–Associated Antigen 4 Blockade and Interleukin 2: A Phase I/II Study

Abstract: Background-Cytotoxic T lymphocyte-associated antigen (CTLA)-4 can inhibit T-cell responses and is involved in tolerance against self antigens. We previously reported autoimmune manifestations and objective cancer regressions in patients with metastatic melanoma treated with CTLA-4 blockade. The possibility of activating tumor-reactive T cells while removing inhibitory activity with CTLA-4 blockade has stimulated interest in using anti-CTLA-4 antibodies in combination with other cancer immunotherapies to improv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
282
1
8

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 470 publications
(298 citation statements)
references
References 25 publications
7
282
1
8
Order By: Relevance
“…19,22,23,28,[30][31] The evidence that IPI treatment of MM patients can upregulate the frequency in the periphery of memory/activated T cell subsets was also observed in our study. [24][25][26][27][28] Taken together these observations corroborate the hypothesis that changes of the frequency of circulating T cell subsets from patients enrolled in the NIBIT-M1 study resulted from the activity of the checkpoint blockade agent and were not affected by chemotherapy.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…19,22,23,28,[30][31] The evidence that IPI treatment of MM patients can upregulate the frequency in the periphery of memory/activated T cell subsets was also observed in our study. [24][25][26][27][28] Taken together these observations corroborate the hypothesis that changes of the frequency of circulating T cell subsets from patients enrolled in the NIBIT-M1 study resulted from the activity of the checkpoint blockade agent and were not affected by chemotherapy.…”
Section: Discussionsupporting
confidence: 76%
“…Similar observations were previously reported for IPI treatment of MM patients, though no association with the patients' clinical outcome was found. [24][25][26][27][28] The detailed phenotypic analysis carried out in PBMCs of patients enrolled in the NIBIT-M1 study allowed to identify for the first time multiple circulating T cell subsets, including memory/activated and Th17 T cells, which frequency in the circulation either at baseline or at W12 post-treatment was associated with the clinical outcome of MM patients. The analysis of the frequency at W24 post-treatment of T cell subpopulations in PBMCs of MM patients was informative for the identification of T lymphocytes persisting in the circulation in the course of treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, one study performed in mice revealed an essential role of IL-2 in mediating the antitumor activity of CTLA-4 blockade [28]. Moreover, a clinical trial showed that the therapeutic effects of CTLA-4 blockade against melanoma were not improved by simultaneous treatment with recombinant IL-2 (rIL-2) [29], suggesting that both treatments may act through the same pathway. Our results here uncover a key role for IL-2 and several components of the IL-2R complex (CD25 and CD122) in the antitumor effects of anti-CTLA-4 antibodies in murine colon cancer and sarcoma models.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to a 14% response rate, numerous immune-mediated side effects were seen, including nephritis, hepatitis, uveitis, panhypophysitis, dermatitis, and enterocolitis. Clinical trials using ipilimumab combined with a peptide vaccine showed antitumor activity in patients with melanoma, though severe but reversible immune breakthrough events (IBE) were seen [62].…”
Section: Vaccine and Anti-clta-4 Monoclonal Antibody (Mab)mentioning
confidence: 99%